PENGARUH WORD OF MOUTH, HARGA DAN KUALITAS PRODUK TERHADAP BRAND IMAGE PADA PERUSAHAAN PT. KALBE FARMA SURAKARTA - Arif Wieko; Edi Purwanto; Ngaisah (ITB AAS Indonesia Surakarta, 2025)
This study aims to examine the significance of the influence of Word of Mouth (X1) on Brand Image (Y) of PT. Kalbe Farma Surakarta, the influence of Price (X2) on Brand Image (Y) of PT. Kalbe Farma Surakarta, the influence of Product Quality (X3) on Brand Image (Y) of PT. Kalbe Farma Surakarta, the simultaneous influence of Word of Mouth (X1), Price (X2), and Product Quality (X3) on Brand Image (Y) of PT. Kalbe Farma Surakarta, and to identify which variable has the most dominant effect on Brand Image (Y) of PT. Kalbe Farma Surakarta. The results of the study conclude that the multiple linear regression equation is: Y = -2.393 + 0.629X1 + 0.467X2 + 0.273X3.The t-test analysis for Word of Mouth shows a t-value of 8.871 > t-table 1.986, thus Ho is rejected. This indicates that Word of Mouth has a positive and significant effect on the Brand Image of PT. Kalbe Farma Surakarta (Y). The t-test analysis for Price (X2) shows a t-value of 8.053 > t-table 1.986, thus Ho is rejected. This indicates that Price has a positive and significant effect on the Brand Image of PT. Kalbe Farma Surakarta (Y). The t-test analysis for Product Quality (X3) shows a t-value of 4.976 > t-table 1.986, thus Ho is rejected. This indicates that Product Quality has a positive and significant effect on the Brand Image of PT. Kalbe Farma Surakarta (Y). Based on the F-test analysis, the F-value is 117.730 > F-table 2.311, thus Ho is rejected, meaning that simultaneously Word of Mouth (X1), Price (X2), and Product Quality (X3) have a significant effect on the Brand Image of PT. Kalbe Farma Surakarta (Y).The coefficient of determination (R²) is 0.780 or 78%, meaning that Word of Mouth (X1), Price (X2), and Product Quality (X3) together influence the Brand Image of PT. Kalbe Farma Surakarta (Y) by 78%, while the remaining 22% is influenced by other factors not examined in this study, such as facilities, technology, location, and others. Kata kunci : Word of mouth, Product Quality, Brand Image